![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x^2-2y\right)^3=27x^6-54x^4y+36x^2y^2-8y^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(3x^2-2y^3\right)^2\)
\(=\left(3x^2\right)^2-2\cdot3x^2\cdot2y^3+\left(2y^3\right)^2\)
\(=9x^4-12x^2y^3+4y^6\)
b) \(\left(-2x^2-3\right)^2\)
\(=\left(-2x^2\right)^2-2\cdot\left(-2x^2\right)\cdot3+3^2\)
\(=4x^4+12x^2+9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,\(\left(x^2+2xy\right)^3=\left(x^2\right)^3+3.\left(x^2\right)^2.2xy+3.\left(2xy\right)^2.x^2+\left(2xy\right)^3\)
\(=x^6+6x^5y+12x^4y^2+8x^3y^3\)
b,\(\left(3x^2-2y\right)^3=\left(3x^2\right)^3-3.\left(3x^2\right)^2.2y+3.\left(2y\right)^2.3x^2-\left(2y\right)^3\)
\(=27x^6-54x^4y+36y^2x^2-8y^3\)
c,\(\left(2x^3-y^2\right)^3=8x^9-12x^6y^2+6x^3y^4-y^6\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x^2+2xy\right)^3\)
\(=\left(x^2\right)^3+3\left(x^2\right)^22xy+3x^2\left(2xy\right)^2+\left(2xy\right)^3\)
\(=x^6+6x^5y+12x^4y^2+8x^3y^3\)
b) \(\left(3x^2-2y\right)^3\)
\(=\left(3x^2\right)^3-3\left(3x^2\right)^22y+3.3x^2\left(2y\right)^2-\left(2y\right)^3\)
\(=27x^6-54x^4y+36x^2y^2-8y^3\)
c) \(\left(2x^3-y^2\right)^3\)
\(=\left(2x^3\right)^3-3\left(2x^3\right)^2y^2+3.2x^3\left(y^2\right)^2-\left(y^2\right)^3\)
\(=8x^9-12x^6y^2+6x^3y^4-y^6.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a. $=(2x)^2-2.2x.5y+(5y)^2=4x^2-20xy+25y^2$
b. $=(3x)^2+2.3x.2y+(2y)^2=9x^2+12xy+4y^2$
c. $=(4y+3x)(4y-3x)=(4y)^2-(3x)^2=16y^2-9x^2$
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1: \(3x+2\left(5-x\right)=0\)
\(\Rightarrow3x+10-2x=0\)
\(\Rightarrow x+10=0\)
\(\Rightarrow x=-10\).
Câu 2: \(2x\left(5-3x\right)+2x\left(3x-5\right)-3\left(x-7\right)=3\)
\(\Rightarrow2x\left(5-3x\right)-2x\left(5-3x\right)-3\left(x-7\right)=0\)
\(\Rightarrow\left(2x-2x\right)\left(5-3x\right)-3\left(x-7\right)=3\)
\(\Rightarrow-3\left(x-7\right)=3\)
\(\Rightarrow x-7=-1\)
\(\Rightarrow x=6.\)
Câu 3:
Áp dụng hằng đẳng thức mở rộng có:
\(\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)\)
\(=a^3+b^3+c^3-3abc.\)
Câu 4: \(3x^2\left(3x^2-2y^2\right)-\left(3x^2-2y^2\right)\left(3x^2+2y^2\right)\)
\(=\left(3x^2-2y^2\right)\left[3x^2-\left(3x^2+2y^2\right)\right]\)
\(=\left(3x^2-2y^2\right)\left(-2y^2\right)\)
\(=-6x^2y^2+4y^3.\)
Câu 5:
Ta có: \(R=\left(2x-3\right)\left(4+6x\right)-\left(6-3x\right)\left(4x-2\right)\)
\(=\left(8x-12+12x^2-18x\right)-\left(24x-12x^2-12+6x\right)\)
\(=12x^2-10x-12-24x+12x^2+12-6x\)
\(=24x^2-40x.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,\(\left(2x-1\right)\left(4x^2+2x+1\right)=\left(2x-1\right)\left[\left(2x\right)^2+2x.1+1^2\right]\)
\(=\left(2x\right)^3-1=8x^3-1\)
b,\(\left(x+2y+z\right)\left(x+2y-z\right)=\left(x+2y\right)^2-z^2\)
\(=x^2+2.x.2y+\left(2y\right)^2-z^2=x^2+4xy+4y^2-z^2\)
`a)(2x-1)(4x^2+2x+1)`
`=(2x-1)[(2x)^2+2x.1+1^2]`
`=(2x)^3-1^3`
`=8x^3-1`
Áp dụng HĐT:`A^3-B^3=(A-B)(A^2+AB+B^2)`
`b)(x+2y+z)(x+2y-z)`
`=[(x+2y)+z][(x+2y)-z]`
`=(x+2y)^2-z^2`
`=x^2+2.x.2y+(2y)^2-z^2`
`=x^2+4xy+4y^2-z^2`
Áp dụng HĐT:`A^2-B^2=(A+B)(A-B)`
`(A+B)^2=A^2+2AB+B^2`
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(2x-1\right)\left(4x^2+2x+1\right)=8x^3-1\)
b) \(\left(x+2y+z\right)\left(x+2y-z\right)=\left(x+2y\right)^2-z^2\)
\(\left(3x-2y\right)^2=9x^2-12xy+4y^2.\)